Relation Between Plasma Leptin and Premenstrual Syndrome In Young Girls - FARIHA ASGHAR M. A. SULTAN, SAGHIR AKHTAR ALI (Journal of Fatima Jinnah Medical University, 2018)
The purpose of the study was to investigate the relationship of leptin with body mass index based categories in different phases of menstrual cycles of both normal and premenstrual syndrome (PMS) symptoms. Female subjects (no=114; age:20± 1.94,19-2Iyears), were included to obtain information about their anthropometric profiles (subjects were categorized on the basis of their BMI) and PMS symptoms on a specified prescribed questionnaire and fasting blood samples were collected during specific days of follicular and luteal phases. The presumptive day of ovulation to identify the phases was detected by using biphasic BBT patterns. Plasma leptin levels were determined by EIA using commercially available Kits. Circulating leptin concentrations varied during the different phases of normal menstrual cycle; slightly higher but significant values during the luteal phase compared to the follicular phase only in subjects with less than 26.8 BM!. Further, PMS subjects depicted significantly higher plasma leptin levels (p<0.001) in both follicular and luteal phases compared to their corresponding controls of all the categories of BM!. The increased level of leptin in PMS subjects; suggest it could have an important role in the pathophysiology of PMS.